Biogas production from biodiesel production residues in Brazil - a review - Honório, Glaucio (Latin American Journal of Energy Research, 2024)
Problems linked to the burning of fossil fuels combined with growing global demand have contributed to society's search for alternative and sustainable sources of energy, mainly from biomass, where biodiesel stands out. During its production process, glycerol is the main by-product formed and can be absorbed by various industries. However, the growth in production has led to a saturation of the market with glycerol, and finding ways to use this residue becomes essential. The present study seeks to clarify the use of residual glycerin as a substrate for anaerobic co-digestion in the production of biogas, another source of renewable energy, which has been widely studied in the search for a more sustainable future, reducing the consumption of natural gas. As presented, the use of glycerol associated with various waste improves the production of biogas, especially methane, constituting a promising way to dispose of this waste.
Keywords: biogas; biodiesel; glycerol; anaerobic codigestion